2013
DOI: 10.4049/jimmunol.1301195
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term IgG Response to Porcine Neu5Gc Antigens without Transmission of PERV in Burn Patients Treated with Porcine Skin Xenografts

Abstract: Acellular materials of xenogenic origin are used worldwide as xenografts and Phase I trials of viable pig pancreatic islets are currently being performed. However, limited information is available on transmission of porcine endogenous retrovirus (PERV) after xenotransplantation and on the long-term immune response of recipients to xenoantigens. We analyzed the blood of burn patients who had received living pig skin dressings for up to 8 weeks for the presence of PERV as well as for the level and nature of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
126
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 118 publications
(132 citation statements)
references
References 64 publications
6
126
0
Order By: Relevance
“…Furthermore, our sera were diluted to 1:100 (instead of 1:2), diluting other potential antibodies, and with final anti-Neu5Gc concentration close to that of the unaffected individual's sera. As mentioned previously, anti-Neu5Gc epitope recognition by serum IgG drastically differs between primed and unprimed individuals (26). Therefore, different patterns of Neu5Gc epitopes recognized by elicited anti-Neu5Gc antibodies in primed individuals, as in our study, in addition to exposure to increased levels of anti-Neu5Gc, may be important in understanding a potential role of such antibodies in this unique situation of a "physiological" immune complex condition.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Furthermore, our sera were diluted to 1:100 (instead of 1:2), diluting other potential antibodies, and with final anti-Neu5Gc concentration close to that of the unaffected individual's sera. As mentioned previously, anti-Neu5Gc epitope recognition by serum IgG drastically differs between primed and unprimed individuals (26). Therefore, different patterns of Neu5Gc epitopes recognized by elicited anti-Neu5Gc antibodies in primed individuals, as in our study, in addition to exposure to increased levels of anti-Neu5Gc, may be important in understanding a potential role of such antibodies in this unique situation of a "physiological" immune complex condition.…”
Section: Discussionmentioning
confidence: 76%
“…However, anti-Gal antibody levels were not increased, arguing against this interpretation. In addition, as elicited anti-Neu5Gc antibodies recognize different patterns of Neu5Gc epitopes than "natural" ones (26) and their presence results in increased long-term exposure of Neu5Gc-positive ECs to these antibodies, they may trigger a chronic inflammation of graft vascular walls, as further discussed below. Indeed, in Cmah KO mice, an animal model unable to biosynthesize Neu5Gc, similarly to humans, it has been demonstrated that anti-Neu5Gc antibodies can stimulate chronic inflammation in dietary Neu5Gc-charged tissues (36).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although PERVs were shown to be able to infect human cells in vitro (8), to date there is no evidence of transmission to recipients of xenografts (63)(64)(65)(66)(67)(68), apparently due to an efficient protective mechanism of the recipient. Epigenetic silencing is a common mechanism of host protection against retroviral infection; however, here we show that human cells are very inefficient in PERV silencing by DNA methylation.…”
Section: Discussionmentioning
confidence: 99%